A new contraction mapping principle in partially ordered metric spaces and applications to ordinary differential equations - Yan, Fangfang; Su, Yongfu; Feng, Qiansheng (Fixed point theory and algorithms for sciences and engineering, 2012)
The aim of this paper is to extend the results of Harjani and Sadarangani and some other authors and to prove a new fixed point theorem of a contraction mapping in a complete metric space endowed with a partial order by using altering distance functions. Our theorem can be used to investigate a large class of nonlinear problems. As an application, we discuss the existence of a solution for a periodic boundary value problem.